Determining Optimum Oil Separator Size and Optimum Operating Pressure - Al-Zubaidy, Ghanim Madeeh (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
The optimum separators operating pressure is determined by using flash calculations and equilibrium ratios. In this study, the optimum separator size for Jambur field is calculated by using equations introduced by Arnold and Stewart and API12J Specification [1]. Because Jambur field has a high production rate two conditions are taken in the study to determine separator size, first based on production rate 80,000 bbl/day and second based on split the production between two banks A and B (40,000 bbl/day for each bank). The calculation resulted in optimum separator pressure for the first stage of 700 psi, and the second stage of 300 psi, and the third stage of 120 psi. The results show that as the number of stages increased above three-stage for Jambur field less incremental liquid recovery achieved and this will not cover the cost of adding an extra stage.